2018
DOI: 10.1128/aac.01682-18
|View full text |Cite
|
Sign up to set email alerts
|

The Combination of Fosfomycin plus Meropenem Is Synergistic for Pseudomonas aeruginosa PAO1 in a Hollow-Fiber Infection Model

Abstract: Treating high-density bacterial infections is a challenging clinical problem. We have a paucity of new agents that can address this problem. Pseudomonas aeruginosa is a particularly difficult pathogen to treat effectively because of the plethora of resistance mechanisms it carries. Fosfomycin is an agent discovered circa 40 years ago. Recently, it has been resurrected in the United States and studied for intravenous therapy. We hypothesized that, to maximize its utility, it would require combination chemothera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 16 publications
0
24
0
Order By: Relevance
“…2). This system can simulate virtually any time course of drug concentrations for one or multiple drugs with the same or different half-lives (2730). Multiexponential profiles can be simulated by switching the pump rates at appropriate times (31).…”
Section: In Vitro Pk/pd Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…2). This system can simulate virtually any time course of drug concentrations for one or multiple drugs with the same or different half-lives (2730). Multiexponential profiles can be simulated by switching the pump rates at appropriate times (31).…”
Section: In Vitro Pk/pd Modelsmentioning
confidence: 99%
“…While MB and QSP models both implement the mechanism(s) of drug action or mechanism(s) of resistance or both, QSP models usually describe multiple different types of experimental observations to characterize these mechanisms in more depth. Both of these models can simultaneously describe and predict the time course of bacterial killing and resistance emergence, and both have been developed for antibiotic monotherapy and combinations (9, 10, 14, 15, 30, 31, 33, 34, 40, 41, 55, 56, 58, 71, 72, 7684). These models incorporate genotypic resistance development by multiple bacterial populations with different susceptibilities and phenotypic tolerance of slowly replicating bacteria.…”
Section: Considerations For Design and Conduct Of In Vitro Pk/pd Modelsmentioning
confidence: 99%
“…Time-kill curves with colistin alone showed a similar pattern in all the isolates, with an initial 3 to 5 log 10 reduction after 2 h, followed by regrowth in all cases. In 11 isolates (ST111 , ST175 [10][11][12][13][14][15][16][17][18][19][20][21][22][23] All isolates treated with the C/T plus colistin combination showed an initial 2-to 5-log 10 CFU/ml reduction followed by a plateau. The combination had bactericidal effect in all cases, a synergistic effect at 24 .…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have recommended antibiotic therapy combining an antipseudomonal ␤-lactam and an aminoglycoside or fluoroquinolone (16)(17)(18)(19)(20). Data on combinations containing C/T, however, are scarce (21)(22)(23)(24).…”
mentioning
confidence: 99%
“…Hamou-Segarra et al evaluated P. aeruginosa mutant isolates defective in several components of the peptidoglycan recycling system exposed to fosfomycin and imipenem alone or in combination and showed that the hyperproduction of AmpC significantly increased susceptibility to fosfomycin (30). Using a hollow-fiber infection model, Drusano et al evaluated the activity of meropenem and fosfomycin against P. aeruginosa at a high inoculum (8.18 log 10 CFU/ml) and demonstrated that the combination resulted in significant synergism and was also able to contain the amplification of the subpopulation of mutants resistant to both antimicrobials; the authors speculated that the different mechanisms of action of the agents and the AmpC hyperproduction, commonly expressed in the presence of carbapenems, could be responsible for these positive effects (31).…”
Section: Discussionmentioning
confidence: 99%